2023
DOI: 10.3389/fpubh.2023.1163484
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of immersive head-mounted virtual reality among older nursing home residents

Abstract: IntroductionVirtual Reality (VR) is a tool that is increasingly used in the aging population. Head-Mounted Displays (HMDs) are stereoscopic vision devices used for immersive VR. Cybersickness is sometimes reported after head-mounted display (HMD) VR exposure. Cybersickness severity and anxiety state reflect VR low tolerance. We aimed to evaluate HMD VR tolerance among older nursing home residents through cybersickness and anxiety state.MethodsA total of 36 participants were included in this preliminary study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…This may include bigger font sizes, easier interfaces, and simple controllers (Ijaz et al, 2016). Furthermore, so called "cybersickness" is a term used in VR research to describe the dizziness that can arise when being immersed in virtual reality, especially for older adults (Rmadi et al, 2023). However, other studies have not found their subjects to experience cybersickness to a minimal extent or not at all (Campo-Prieto et al, 2022; Riaz et al, 2021).…”
Section: Not For the With Cognitive Declinementioning
confidence: 99%
“…This may include bigger font sizes, easier interfaces, and simple controllers (Ijaz et al, 2016). Furthermore, so called "cybersickness" is a term used in VR research to describe the dizziness that can arise when being immersed in virtual reality, especially for older adults (Rmadi et al, 2023). However, other studies have not found their subjects to experience cybersickness to a minimal extent or not at all (Campo-Prieto et al, 2022; Riaz et al, 2021).…”
Section: Not For the With Cognitive Declinementioning
confidence: 99%